2019
DOI: 10.1016/j.celrep.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Activation Gene-3 Maintains Mitochondrial and Metabolic Quiescence in Naive CD4+ T Cells

Abstract: Highlights d LAG-3 limits CD4 + T cell oxygen consumption and spare respiratory capacity (SRC) d Naive CD4 + T cells utilize their SRC to support spontaneous proliferation d LAG-3 regulates STAT5 and Akt activation d Lag3 À/À CD4 + T cells are less dependent upon IL-7 for survival and metabolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 49 publications
1
55
0
Order By: Relevance
“…Some work has begun to show that these molecules may also signal in a tonic tonic fashion, which may regulate T cell function. For instance, Previte and colleagues investigated the role of the inhibitory lymphocyte activation gene‐3 (LAG‐3) in controling naïve T cell metabolism . In their work, the authors found that genetic deletion of LAG‐3 induced T cells to be more metabolically active and more proliferative under homeostatic conditions in an adoptive transfer model.…”
Section: Outlook: Tonic Signals and Cancer Immunotherapy?mentioning
confidence: 99%
“…Some work has begun to show that these molecules may also signal in a tonic tonic fashion, which may regulate T cell function. For instance, Previte and colleagues investigated the role of the inhibitory lymphocyte activation gene‐3 (LAG‐3) in controling naïve T cell metabolism . In their work, the authors found that genetic deletion of LAG‐3 induced T cells to be more metabolically active and more proliferative under homeostatic conditions in an adoptive transfer model.…”
Section: Outlook: Tonic Signals and Cancer Immunotherapy?mentioning
confidence: 99%
“…Recently chronic stimulation of adaptive NKG2C+ NK cells in vitro led to a marked induction of checkpoint inhibitory receptors PD-1 and lymphocyte activation gene-3 (LAG-3) sharing epigenetically driven programmes with exhausted CD8 T cells (Merino et al, 2019). Moreover, a role for LAG-3 in regulating CD4 T cell metabolism and mitochondrial biogenesis has been identified (Previte et al, 2019). We have previously reported a modest increase in the levels of PD-1 expression on NK cells in HIV-1 infection (Peppa et al, 2018), however, the role of inhibitory receptors in controlling NK cell metabolism remains to be further defined.…”
Section: Discussionmentioning
confidence: 99%
“…LAG-3 was shown to modulate bioenergetics of T cells. Specifically, expression of LAG-3 on CD4 + T cells inhibited mitochondrial biogenesis and metabolism [91]. LAG-3-deficient T cells were also more glycolytically active than wild-type T cells.…”
Section: Lag-3mentioning
confidence: 95%